Positive Modeling and Empowerment as a Central Factor of Successful Academic Mentoship - Civić, Aila (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Mentorship has been gaining importance lately, as it plays a key role in achieving career goals, especially in academia. Through various forms of mentoring in the academic environment, both the mentor and the mentee gain valuable experience that can have a significant impact on their professional role in a particular field. However, there can be a number of challenges in mentoring, which vary depending on the impact of intertwined factors such as gender, empathy, communication, and more. We often neglect that planning is the foundation of any successful process, and it is necessary to highlight any significant obstacles that might arise and suggest ways to resolve them. In contemporary literature, there is a growing emphasis on linking mentoring with positive modeling and empowerment. In this paper, we aim to explore the barriers faced by mentors and mentees in the academic environment, how positive modeling can contribute to a more successful mentoring relationship, and the role of empowerment in such collaboration. In the chapter Results and discussion, based on the findings of various authors, we will provide proposals for measures to solve challenges that can effectively contribute to a more successful mentoring relationship based on positive modeling and empowerment.